Revalidation of Ptychophallus campylus Pretzmann, 1968, a freshwater crab species from Costa Rica (Brachyura: Decapoda: Pseudothelphusidae) - Magalhães, Célio; Wehrtmann, Ingo S.; Mantelatto, Fernando L. (Revista de Biología Tropical, 2025)
Introduction: Freshwater crab diversity in the Neotropics is high, comprising three families: Epiloboceridae, Pseudothelphusidae and Trichodactylidae. The genus Ptychophallus consists of 13 species, all from Panama and Costa Rica. Ptychophallus campylus has not been recognized as a valid species and has been treated as a presumptive junior synomym of Ptychophallus tristani. Objective: The present study aims to formalize the resurrection of P. campylus as a valid species. Methods: An additional specimen of P. campylus collected in the province of Limón, Costa Rica, was analyzed and compared to both the holotype of P. campylus and the description of P. tristani. Results: The gonopod 1 of P. campylus is morphologically similar to that of P. tristani but can be differentiated by the shape of the lateral process of the male first gonopod. Moreover, both species show different geographic distributions: whereas P. tristani occurs in hydrographic basins of the Pacific versant of Costa Rica, P. campylus seems to be restricted to the Caribbean slope in eastern Costa Rica. Conclusions: Ptychophallus campylus is formally revalidated from the synonymy of P. tristani, confirming recently published results of multigene analysis that recovered both species in different lineages. This revalidation of P. campylus increases the number of valid species of the genus Ptychophallus to a total of 14, with nine species or 64.2% of all Ptychophallus species occurring in Costa Rica.